Faktor-Faktor yang Berhubungan Dengan Pembelajaran Di Masa Pandemi Covid-19 - Rian Maylina Sari; Mefrie Puspita; Lusi Oktaviana Murdian (LPPM STIKes Panca Bhakti Bandar Lampung, 2022)
The Covid-19 pandemic in Indonesia has an impact on education, so online learning is carried out. Learning becomes less effective because of these obstacles. Factors that influence the success of online learning are the role of the family, student motivation, and the role of the teacher. This study aims to determine the factors related to learning during the Covid-19 pandemic. This research is a quantitative research with a cross sectional research design. The population in this study were all students of SD Negeri 001/IV Jambi City in grades 4 and 5, totaling 338 students with a total sample of 180 using proportional random sampling technique. The survey was conducted from 12 to 24 July. This tool uses a survey through Google Forms and univariate and bivariate analysis with chi-square test. The results showed that there was a relationship between the role of the family (p = 0.001), student motivation (p = 0.000), and the role of the teacher (p = 0.000) during the pandemic learning process. We can conclude that the role of the family, motivation, and the role of the teacher are related to the learning process during the pandemic